13-(x+8)=6x+2

Simple and best practice solution for 13-(x+8)=6x+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13-(x+8)=6x+2 equation:


Simplifying
13 + -1(x + 8) = 6x + 2

Reorder the terms:
13 + -1(8 + x) = 6x + 2
13 + (8 * -1 + x * -1) = 6x + 2
13 + (-8 + -1x) = 6x + 2

Combine like terms: 13 + -8 = 5
5 + -1x = 6x + 2

Reorder the terms:
5 + -1x = 2 + 6x

Solving
5 + -1x = 2 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
5 + -1x + -6x = 2 + 6x + -6x

Combine like terms: -1x + -6x = -7x
5 + -7x = 2 + 6x + -6x

Combine like terms: 6x + -6x = 0
5 + -7x = 2 + 0
5 + -7x = 2

Add '-5' to each side of the equation.
5 + -5 + -7x = 2 + -5

Combine like terms: 5 + -5 = 0
0 + -7x = 2 + -5
-7x = 2 + -5

Combine like terms: 2 + -5 = -3
-7x = -3

Divide each side by '-7'.
x = 0.4285714286

Simplifying
x = 0.4285714286

See similar equations:

| 14.25/5 | | 14.25/4 | | 0.75x+.05(2-x)=10(43) | | -2(x+6)=0,5-14 | | 3x^2=5-2 | | 8399840909205709x=897979070979797009-5 | | 9=-27+4x | | -7-6x+2=-(x-4).+2(x+6) | | 4/3x=-3 | | -3(2t-5)+2t=5t | | 10=-27+4x | | 2x^2+4ax+3x+6a=0 | | 3468666765x-558575858=68687763456789+56789 | | 2x/5=-2 | | (3-x).5+8=18 | | 2x/5 | | -84-10x=56-38x | | 2x+37=4x+1 | | 300-2x=50+5x | | X^3-52-96=0 | | y=-27+4x | | 2(2x-1)-3(x-5)=5x-3(2x-7)+8 | | y+8y=8 | | y+8y=7 | | 5x=-32.15 | | -4x+2y=0 | | -7(1-v)-5(v-3)=-7v+5v | | (2x+2y)+(x+y)=180 | | 7x^2-12x-27=0 | | 1.5lnx=0 | | 23m-8-2m-6= | | 3+3n-1=6n+2-2n |

Equations solver categories